Does Loyalty Matter? Impact of Brand Loyalty and Sales Promotion on Brand Equity. Issue 4 (6th June 2020) - Joseph, Joshy; Sivakumaran, Bharadhwaj; Mathew, Shawn
Abstract: Brand Equity erosion due to non-consumer franchise building (non-CFB) sales promotions have been a recurring theme in extant literature. However, the disproportionate increase in non- CFB promotion activities by companies contradicts this academic view. This research provides a rationale for this inconsistency by examining the moderating impact of brand loyalty on the promotion – brand equity relationship. Results indicate that loyalty moderates the promotion-brand equity relationship, and even short term promotions enhance brand equity in certain market segments (like those dominated by spurious loyals). Practitioners can target specific loyalty groups through short term promotions without impacting Brand Equity.